Population dynamics in mixed canopies composed of kikuyu-grass and tall fescue - Miqueloto T.* (2020)
© 2020 by the authors.The current work was based on the central hypothesis that grazing management strategies modulate tillering dynamics of mixed canopies composed of kikuyu-grass (C4 perennial grass) and tall fescue (C3 perennial grass). Among the five grazing management conditions evaluated, three (7, 12, and 17 cm) represented the heights up to which the grasses were kept by mimicking a continuous stocking method throughout the experimental period (from May 2016 to October 2017), and the other two consisted of the heights 12 and 17 cm with a single grazing to 7 cm in mid-autumn. Nitrogen fertilization was applied only during winter-spring. The results showed that under severe grazing (7 cm), kikuyu-grass predominated in the area and that tall fescue population predominated in the moderately lenient (12 cm) and lenient (17 cm) grazed pastures, regardless of an occasional autumn grazing to 7 cm. After two years of evaluation, kikuyu-grass tillers were reduced to 6% of the total population in those pastures managed at the heights of 12 and 17 cm. Grazing management strategies modulate species proportions in a mixed canopy composed of kikuyu and tall fescue. Moreover, our data also suggest that it seems unlikely that there is a stable association of tall fescue and kikuyu-grass when no nitrogen fertilization is applied during summer.